Lung cancer mortality in Australia in the twenty-first century: How many lives can be saved with effective tobacco control?. (April 2019) - Luo, Qingwei; Steinberg, Julia; O'Connell, Dianne L.; Yu, Xue Qin; Caruana, Michael; Wade, Stephen; Pesola, Francesca; Grogan, Paul B.; Dessaix, Anita; Freeman, Becky; Dunlop, Sally; Sasieni, Peter; et al.
Highlights: Quantified the number of lung cancer deaths averted in Australia through tobacco control. Almost 2 million lung cancer deaths have already been prevented over the period 1956–2100. Lung cancer will continue to be a significant public health concern in Australia. Achieving zero smoking by 2025 would result in 360, 000 more lung cancer deaths being averted by 2100. Highlighted the urgent need for more effective and targeted tobacco control strategies to be implemented. Abstract: Objectives: To estimate the number of past and future lung cancer deaths that have already been averted by tobacco control initiatives in Australia, and to estimate the number of additional deaths averted under various smoking scenarios. Methods: We predicted lung cancer mortality rates and case numbers to 2100 using a previously validated generalized linear model based on age, birth cohort and population cigarette smoking exposure. We estimated the impact of various tobacco control scenarios: 'actual tobacco control' (incorporating the aggregate effect of past and current taxation, plain packaging, mass media campaigns and other initiatives) and scenarios where 10%, 5% and 0% smoking prevalence was achieved by 2025, all of which were compared to a counterfactual scenario with the highest historical smoking consumption level continuing into the future as if no tobacco control initiatives had been implemented. Results: Without tobacco control, there would have been an estimated 392, 116 lung cancer deaths over the period 1956–2015; of these 20% (78, 925 deaths; 75, 839 males, 3086 females) have been averted due to tobacco control. However, if past and current measures continue to have the expected effect, an estimated 1.9 million deaths (1, 579, 515 males, 320, 856 females; 67% of future lung cancer deaths) will be averted in 2016–2100. If smoking prevalence is reduced to 10%, 5% or 0% by 2025, an additional 97, 432, 208, 714 or 360, 557 deaths could be averted from 2016 to 2100, respectively. Conclusion: Tobacco control in Australia has had a dramatic impact on the number of people dying from lung cancer. Several hundred thousand more lung cancer deaths could be averted over the course of the century if close-to-zero smoking prevalence could be achieved in the next decade.